Endonasal Endoscopic Pituitary Adenoma Resection: Preservation of Neurohypophyseal Function - Masopust, Vaclav; Netuka, David; Benes, Vladimir; Bradac, Ondrej; Marek, Josef; Hana, Vaclav (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Objectives In the past 10 years, endoscopic resection of pituitary adenomas has become an alternative to microsurgical resection with the additional advantage of increasing the patient's postoperative comfort. This analysis explored whether endoscopic resection can reduce the risk of postoperative neurohypophyseal dysfunction.Design We rated and compared the need to administer desmopressin during the first four postoperative days and with the need after a follow-up of at least 3 months (chronic administration).Setting Three groups of patients were compared: Patients in group 1 were operated on microscopically. Patients in group 2 were operated on endoscopically. Patients in group 3 were operated on endoscopically with intraoperative magnetic resonance imaging (iMRI).Participants Group 1 was made up of 50 patients treated in 1999; group 2 comprised 50 patients operated on from 2006 to 2007; and Group 3 comprised 50 patients operated on in 2008.Main Outcome Measures In group 1 the need to use desmopressin postoperatively occurred in eight patients; three needed chronic treatment. In group 2 the need for postoperative application of desmopressin occurred in four patients; none required chronic treatment. In group 3 desmopressin had to be administered postoperatively in five patients but only temporarily.Results and Conclusions Endoscopic surgery is a safe and effective method for the resection of pituitary adenomas. The rate of chronic desmopressin application was reduced. In conjunction with iMRI and navigation, the endoscopic technique allows increased radicality together with fewer adverse effects.
Keywords: endoscopic endonasal resection; pituitary adenoma; diabetes insipidus; postoperative frequency of diabetes insipidus